Ultralow-carbon high-Si austenitic stainless steel welding wire for resisting high-temperature concentrated nitric acid corrosion and application thereof
By developing ultra-low carbon high-Si austenitic stainless steel welding wire to control its chemical composition and structural structure, the problems of insufficient mechanical properties, corrosion resistance and crack resistance of existing welding materials in high-temperature concentrated nitric acid environment are solved, and the excellent performance and good corrosion resistance of weld metal are achieved.
Patent Information
- Application Number
- CN202411780649.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing austenitic stainless steel welding materials are difficult to meet the requirements of excellent mechanical properties, corrosion resistance and crack resistance in high-temperature concentrated nitric acid environment, and there are problems of embrittlement and corrosion in applications in nuclear power and other fields.
A ultra-low carbon high Si austenitic stainless steel welding wire for corrosion resistance to high temperature concentrated nitric acid was developed, with chemical compositions of C≤0.03%, Si 3.5%~4.5%, Cr 18.5%~20.5%, Ni 14.5%~16.0%, N 0.03%~0.12%. By controlling the content of these elements, the formation of carbides and delta ferrite is inhibited, and the structure of weld metal is optimized.
The welding wire shows excellent mechanical properties, corrosion resistance and crack resistance in high-temperature concentrated nitric acid environment, meeting the application needs of nuclear power, petrochemical and other fields. The yield strength, tensile strength and impact properties of weld metal meet or exceed the design requirements, and exhibit low corrosion rate in simulated high-temperature nitric acid solution.
Smart Images

Figure CN119566618A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of welding materials, and specifically relates to an ultra-low carbon high-Si austenitic stainless steel welding wire resistant to high-temperature concentrated nitric acid corrosion and an application thereof, which is suitable for welding structural components used in high-temperature concentrated nitric acid environments in the fields of nuclear power, petrochemicals, etc. Background Art
[0002] As an efficient, clean and economical energy source, nuclear energy has become one of the important development directions in my country's energy field. However, with the continuous increase of my country's installed capacity, a large amount of spent fuel containing uranium, plutonium and fission products generated during the operation of nuclear power plants will cause serious harm to the environment and human body if not promptly and effectively treated. Spent fuel reprocessing refers to the chemical treatment of nuclear fuel that has been irradiated (i.e. burned) in the reactor to remove fission products and recover unused and newly generated nuclear fuel materials. This reprocessing method can greatly improve the utilization rate of nuclear fuel and optimize the management and disposal of nuclear waste. The dissolver is one of the key equipment in the spent fuel reprocessing process. It is in high-concentration, high-radioactive boiling nitric acid for a long time, which puts very high requirements on the mechanical properties and corrosion resistance of the material. Corrosion-resistant high-Si austenitic stainless steel is the key to improving the equipment's resistance to high-temperature concentrated nitric acid corrosion. Compared with the corrosion-resistant high-Si stainless steel base material, the development of its supporting welding materials is relatively lagging. The weld is a rapidly cooled cast structure, which is significantly different from the parent material structure after deformation and solution treatment. Many problems in engineering components are caused by the failure of welded joints. Welding materials are an important factor in determining the performance of welded joints. Therefore, the development of high-quality supporting welding materials is the premise and basis for the further promotion and application of corrosion-resistant high-Si austenitic stainless steel.
[0003] The weld metal should have excellent comprehensive mechanical properties and crack resistance while having good resistance to high temperature concentrated nitric acid corrosion. Generally, austenitic stainless steel weld metal contains about (4.0-5.0) wt.% Si element, which can improve its resistance to nitric acid corrosion. Chinese patent application (publication number CN102319965A) reported an ultra-low carbon austenitic welding wire material for stainless steel welding, with the addition of Cu element and rare earth element Re. Cu-containing steel will form a Cu-rich precipitation phase under irradiation, which is a major mechanism for the embrittlement of nuclear power steel. In theory, the addition of rare earth elements can play a role in desulfurization, but it is easy to agglomerate and form inclusions during ingot smelting and melt welding, which is not conducive to improving the nitric acid corrosion resistance of the weld metal. Therefore, the content and use of Cu and rare earth element Re in nuclear power steel should be strictly limited. The literature (Yi Xiaoping, Yuan Shiwei; Welding test and application of 00Cr14Ni14Si4 (C4) steel, Welding 1997 (9): 17-20) reported an A012Si austenitic stainless steel welding wire, which has high strength of deposited metal and poor plasticity. In addition, the intergranular corrosion test results of the weld joint showed that the annual corrosion amount was as high as 1mm / a. To improve the mechanical properties of the weld metal, it is possible to consider adding an appropriate amount of N element to the welding material, while regulating the δ ferrite content in the weld metal to inhibit the occurrence of welding hot cracks. At present, there are relatively few studies on austenitic stainless steel welding materials for high temperature concentrated nitric acid corrosion worldwide. Austenitic stainless steel welding materials with excellent mechanical properties, corrosion resistance and crack resistance should be designed for high temperature concentrated nitric acid corrosion environment, and can be applied to nuclear power, petrochemical and other fields. Summary of the invention
[0004] The purpose of the present invention is to provide an ultra-low carbon high-Si austenitic stainless steel welding wire resistant to high temperature concentrated nitric acid corrosion and its application, the welding wire has excellent mechanical properties, corrosion resistance and crack resistance, and can be applied to nuclear power, petrochemical and other fields.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] The invention discloses an ultra-low carbon high-Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance. The chemical composition of the welding wire is as follows, measured by weight percentage: C≤0.03%, Mn 0.3%-1.6%, Si 3.5%-4.5%, P≤0.01%, S≤0.01%, Cr 18.5%-20.5%, Ni 14.5%-16.0%, Mo≤1.1%, Nb≤0.15%, N 0.03%-0.12%, Cu≤0.1%, Co≤0.06%, Al≤0.05%, V≤0.05%, and the balance is iron.
[0007] The ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance has the following content of each group of elements:
[0008] a. The Cr content in the welding wire is further set to Cr: 18.5% to 19.0%, or further set to Cr: 19.0% to 19.6%, or further set to Cr: 19.6% to 20.5%;
[0009] b. The Si content in the welding wire is further set to Si: 4.0% to 4.4%;
[0010] c. The Ni content in the welding wire is further set to Ni: 14.5% to 15.0%, or further set to Ni: 15.0% to 16.0%;
[0011] d. The nitrogen content in the welding wire is further set to N: 0.03% to 0.07%, or further set to N: 0.07% to 0.10%, or further set to N: 0.10% to 0.12%;
[0012] e. The Mn content in the welding wire is further set to Mn: 0.3% to 0.9%, or further set to Mn: 0.9% to 1.3%, or further set to Mn: 1.3% to 1.6%;
[0013] f. The Nb content in the welding wire is further set to Nb≤0.02%;
[0014] g. The Mo content in the welding wire is further set to Mo≤0.02%.
[0015] The ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance has the following content of each group of elements:
[0016] a. The Cu content in the welding wire is further set to Cu≤0.05%, or further set to Cu≤0.02%, or further set to Cu≤0.01%;
[0017] b. The Co content in the welding wire is further set to Co≤0.03%, or further set to Co≤0.02%, or further set to Co≤0.01%;
[0018] c. The Al content in the welding wire is further set to Al≤0.02%, or further set to Al≤0.01%;
[0019] d. The V content in the welding wire is further set to V≤0.02%, or further set to V≤0.01%;
[0020] e. The P content in the welding wire is further set to P≤0.005%;
[0021] f. The S content in the welding wire is further set to S≤0.003%.
[0022] The ultra-low carbon high-Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance is applied to the welding of austenitic stainless steel parts used in the nuclear power or petrochemical industry under high temperature concentrated nitric acid environment.
[0023] The application of the ultra-low carbon high-Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance adopts TIG welding in the welding process, the joint form is butt joint, the welding current is 150-200A, the arc voltage is 10-15V, the current type / polarity is direct current positive connection mode, and the welding speed is 0.05-0.15m / min.
[0024] The ultra-low carbon high-Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance is used to weld the test piece by a multi-layer and multi-pass deposition method, and the interlayer temperature during the welding process is lower than 100°C.
[0025] The application of the ultra-low carbon high-Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance selects a welding wire with a specification of Φ2.0mm for the welding process.
[0026] In the application of the ultra-low carbon high-Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance, during the welding process, high-purity argon gas with a volume purity of ≥99.995% is used for arc protection, and the argon gas flow rate is 12-20L / min.
[0027] The room temperature tensile properties of the weld metal obtained after welding are as follows: yield strength R p0.2 ≥210MPa, tensile strength R m ≥530MPa, elongation A≥30%; room temperature impact performance: Akv2≥35J; weld metal structure requirements: austenite + delta ferrite two-phase structure, FN value 1~10.
[0028] In the application of the ultra-low carbon high-Si austenitic stainless steel welding wire resistant to high temperature concentrated nitric acid corrosion, the corrosion rate of the weld metal is ≤0.3mm / a after being immersed in a nitric acid solution with a molar concentration of 6M at 95°C under simulated medium conditions until the corrosion rate stabilizes.
[0029] The reasons for determining the chemical composition of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance in the present invention are as follows:
[0030] In the high-temperature concentrated nitric acid service environment, the formation and coarsening of carbides in the weld are important factors that deteriorate the mechanical properties and corrosion resistance of the weld. Reducing the C content can significantly reduce the formation and coarsening tendency of carbides. N is an austenite-forming element and can inhibit the formation of delta ferrite. Excessive delta ferrite is a harmful structure that deteriorates the impact toughness and corrosion resistance of austenitic steel weld metal. The N element can also form carbides with V, which helps to improve the high-temperature strength and stable structure of heat-resistant steel welds. Therefore, in the present invention, C≤0.03%; N: 0.03%~0.12%, preferably 0.03%~0.07%, or 0.07%~0.10%, or 0.10%~0.12%.
[0031] The addition amount of Si in austenitic stainless steel is usually 0.3% to 0.6%, which plays a deoxidizing role during alloy smelting. When used as a welding material, silicon can improve the fluidity of the molten pool, but too high a silicon content will increase the tendency of welding hot cracks and promote the formation of harmful phases, deteriorating the mechanical properties of the weld metal. For high-temperature and high-concentration nitric acid service environments, Si is a key element to improve the nitric acid corrosion resistance of austenitic stainless steel, but the increase in Si content has a significant effect on the segregation and phase precipitation of the weld metal. Therefore, the control range of Si content in the welding material should be reasonably set. In the present invention, Si: 3.5% to 4.5%.
[0032] Mn is an austenitizing element. Increasing the Mn content in heat-resistant steel can inhibit the formation of high-temperature delta ferrite, but at the same time reduce the A1 transformation temperature and reduce the high-temperature stability of the ferrite matrix. When the Mn content is too high, Mn segregation will occur, forming MnS defects and deteriorating performance. The appropriate amount of Mn element added can make the material have high low-temperature impact toughness while ensuring high strength, and also have strong crack resistance. Therefore, the Mn element is one of the indispensable alloying elements. In the present invention, Mn: 0.30% to 1.6%, preferably 0.3% to 0.9%, or 0.9% to 1.3%, or 1.3% to 1.6%.
[0033] Cr is one of the essential elements for austenitic stainless steel to resist high temperature oxidation and corrosion. Cr can improve the oxidation resistance and corrosion resistance of the material. Cr is dissolved in the matrix to play a role of solid solution strengthening, while improving the hardenability of heat-resistant steel and reducing the critical cooling rate of heat-resistant steel, so that it can obtain a full martensitic structure at a lower cooling rate. However, if the Cr content in the steel is too high, it will promote the formation of high-temperature delta ferrite and cause the coarsening of the corresponding carbide precipitation phase, thereby bringing adverse effects. Therefore, in the present invention, Cr: 18.5% to 20.5%, preferably 18.5% to 19.0%, or 19.0% to 19.6%, or 19.6% to 20.5%.
[0034] Ni is an austenitizing element, similar to Mn. Increasing the Ni content in heat-resistant steel can inhibit the formation of high-temperature delta ferrite, but at the same time reduces the A1 transformation temperature and reduces the high-temperature stability of the ferrite matrix. Increasing the Ni content can improve toughness, but reduce the stability of carbonitrides, accelerate the coarsening of the precipitated phase, reduce tempering resistance (tempering stability, tempering resistance), and lead to deterioration of durability. In addition, under the influence of irradiation, Ni is also an important source of helium formation. Therefore, in the present invention, Ni: 14.5% to 16.0%, and the Ni content is preferably 14.5% to 15.0%, or 15.0% to 16.0%.
[0035] Nb is a common microalloying element in austenitic stainless steel, which can fix free carbon atoms in the matrix, thereby inhibiting the formation of M 23 C6 precipitates at the grain boundary and improves the intergranular corrosion resistance. In addition, Nb can significantly improve the high temperature strength through solid solution strengthening and precipitation strengthening of NbX phase and Z phase. However, there are also reports that Nb strongly segregates between dendrites during the solidification of the welding molten pool and promotes the precipitation of second phases such as Nb (C, N), which has an adverse effect on impact toughness. Therefore, in the present invention, Nb≤0.15%, and the Nb content is preferably Nb≤0.02%.
[0036] Mo is a key element that works together with Cr to improve the local corrosion resistance of austenitic stainless steel. It is also a substitution strengthening element that improves high temperature strength but damages plasticity. For austenitic stainless steel weld metal, Mo segregates in the interdendritic region and promotes the formation of interdendritic precipitation phases, and has a strong interaction with Si elements. The influence of Mo-rich phases should be noted in the study of weld metal structure and performance stability. Therefore, in the present invention, Mo≤1.1%, and the Mo content is preferably Mo≤0.02%.
[0037] Cu will form a Cu-rich precipitate phase under irradiation, which is a major mechanism for causing embrittlement of nuclear power steel. Therefore, the Cu content should be strictly limited. In the present invention, Cu≤0.1%, preferably Cu≤0.05%, or Cu≤0.02%, or Cu≤0.01%.
[0038] Co has a large neutron absorption cross section, which can easily cause Co-containing materials to fail under neutron irradiation conditions. Moreover, the half-life of the radioactive isotope 60Co of Co is as long as 5.26 years. Its influence will be increasingly enhanced with the increase of reactor operation time, not only bringing radioactivity to the equipment and components in the reactor, but also making the pipelines, pumps, valves and other equipment in the primary circuit system radioactive, which will bring many difficulties to the maintenance and waste treatment of nuclear reactor equipment components, and may even endanger personal safety. Therefore, the Co content should be strictly limited. In the present invention, Co≤0.06%, preferably Co≤0.03%, or Co≤0.02%, or Co≤0.01%.
[0039] S and P are harmful impurities in steel, most of which are brought in by raw materials during steelmaking and should be reduced as much as possible. In the welding process, the S content will also increase due to unclean groove cleaning. Too much P content will increase the tendency of cold cracking, and too much S content will increase the tendency of hot cracking. Therefore, the content of S and P elements should be strictly controlled in the chemical composition of the welding wire. In the present invention, S≤0.01%, preferably S≤0.003%; P≤0.01%, preferably P≤0.005%.
[0040] The present invention has the following advantages and beneficial effects:
[0041] 1. The ultra-low carbon high-Si austenitic stainless steel welding wire for high-temperature concentrated nitric acid corrosion environment of the present invention has excellent mechanical properties, concentrated nitric acid corrosion resistance and crack resistance, and can be used for welding key structural components in the fields of nuclear power or petrochemicals. The C content in the welding wire of the present invention is ≤0.03%, which inhibits the formation and coarsening tendency of carbides in the weld. By adding 0.03% to 0.12% of N to compensate for the decrease in strength caused by the reduction in C content, the formation of delta ferrite is inhibited. These two points are crucial to improving the mechanical properties, corrosion resistance and crack resistance of heat-resistant steel welds.
[0042] 2. In the composition and proportion of the welding wire, in addition to strictly controlling the contents of C and Cr, the contents of Ni, Mn, Nb and Mo are also precisely controlled: by limiting the Ni content in the welding wire to 14.5% to 16.0% and the Mn content to 0.3% to 1.6%, the delta ferrite content in the weld metal is controlled to improve the nitric acid corrosion resistance and crack sensitivity of the weld metal. The Nb content in the welding wire of the present invention is controlled to be ≤0.15% and the Mo content is ≤1.1%, ensuring that the weld metal has good mechanical properties while still maintaining excellent corrosion resistance.
[0043] In addition, considering the nuclear application field, the welding wire of the present invention does not add Co and Cu, and reduces the production of the long-lived radioactive isotope 60Co by limiting the impurity Co content to no more than 0.06%, and inhibits the radiation embrittlement of the weld metal by limiting the impurity Cu content to no more than 0.1%.
[0044] 3. The ultra-low carbon high-Si austenitic stainless steel welding wire for high-temperature concentrated nitric acid corrosion environment of the present invention is a solid welding wire. When welding under the protection of inert gas, it can effectively prevent weld oxidation, reduce inclusions in the weld, improve weld quality, and effectively avoid slag contamination of the weld and reduction of weld quality during welding of electrodes and flux-cored wires. Experiments show that when the stainless steel welding wire of the present invention is used in combination with the welding process defined by the present invention for welding, spatter is small, the process is stable, and the process performance is good; and an austenitic weld metal that meets the required mechanical properties, concentrated nitric acid corrosion resistance, and crack resistance can be obtained.
[0045] 4. Experiments show that the weld metal of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosive environment of the present invention meets the following performance requirements: yield strength R p0.2 ≥210MPa, tensile strength R m ≥530MPa, elongation A≥30%; room temperature impact performance requirements: Akv2≥35J; the corrosion rate of the weld metal after being immersed in simulated medium conditions (95℃, nitric acid solution with a molar concentration of 6M) until the corrosion rate stabilizes is ≤0.3mm / a; weld metal structure requirements: austenite + delta ferrite two-phase structure, FN value 1~10. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a schematic diagram of the welding joint form used in the present invention.
[0047] Figure 2 The cross-sectional macroscopic morphology of the weld metal of Comparative Example 1. The upper right picture is an enlarged view of the local crack in the left picture, and the lower right picture is an enlarged view of the local crack in the upper right picture. DETAILED DESCRIPTION
[0048] Taking Φ2.0mm welding wire as an example, a multi-layer multi-pass TIG method (manual tungsten inert gas arc welding) is used to prepare the weld metal of the Φ2.0mm welding wire. The base material is corrosion-resistant high-Si austenitic stainless steel, and the joint form is 12mm thick plate butt welding. The welding parameters are: welding current 150A~200A (specifically 180A here), arc voltage 10V~15V (specifically 12V~13V here), DC positive connection mode, welding speed 0.06m / min~0.15m / min (specifically 0.10m / min here), arc protection uses high-purity argon gas with a volume purity of ≥99.995%, and the argon gas flow rate is 12L / min~20L / min (specifically 15L / min here); the interlayer temperature during the welding process is lower than 100°C, and then samples are taken from the weld metal for mechanical property analysis. Of course, the welding process of the present invention can adjust specific welding parameters for different welding wire diameters.
[0049] The chemical compositions (weight percentage) of the ultra-low carbon high Si austenitic stainless steel welding wires of Examples 1 to 5 and Comparative Examples 1 to 2 are shown in Table 1.
[0050] Table 1 Chemical composition of welding wire (wt.%)
[0051]
[0052]
[0053] Table 2 shows the tensile and impact properties test results of the weld metals of the ultra-low carbon high Si austenitic stainless steel welding wires of Examples 1 to 5 and Comparative Examples 1 to 2 at room temperature.
[0054] Table 2 Room temperature tensile and impact test results of weld metal
[0055]
[0056] The tensile properties test results of the weld metals of the ultra-low carbon high Si austenitic stainless steel welding wires of Examples 1 to 5 and Comparative Examples 1 to 2 at 100°C are shown in Table 3.
[0057] Table 3 100℃ tensile properties test results of weld metal
[0058] <![CDATA[Yield strength Rp 0.2 , MPa]]> Tensile strength Rm, MPa Elongation after break A, % Example 1 372 652 46.8 Example 2 372 621 39.0 Example 3 366 620 38.3 Example 4 307 577 52.8 Example 5 390 625 40.8 Comparative Example 1 303 370 7.5 Comparative Example 2 308 438 7.5
[0059] Weld metal microstructure types and FN values (FN is the δ-ferrite content, and its value represents the volume percentage of δ-ferrite, in %) of ultra-low carbon high-Si austenitic stainless steel welding wires of Examples 1 to 5 and Comparative Examples 1 to 2.
[0060] Table 4 Weld microstructure type and FN value
[0061] Organization Type FN value Example 1 Austenite structure + delta ferrite structure 9.6 Example 2 Austenite structure + delta ferrite structure 8.2 Example 3 Austenite structure + delta ferrite structure 7.1 Example 4 Austenite structure + delta ferrite structure 1.8 Example 5 Austenite structure + delta ferrite structure 1.3 Comparative Example 1 Fully austenitic structure 0 Comparative Example 2 Austenite structure + delta ferrite structure 0.5
[0062] The corrosion performance of the weld metal of the ultra-low carbon high-Si austenitic stainless steel welding wire of Examples 1 to 5 is shown in Table 5. The corrosion solution is a 6M nitric acid solution, and the weld metal is soaked at 95°C for 120 hours, then taken out, cleaned and weighed, and the corrosion rate is calculated.
[0063] Table 5 Corrosion rate of weld metal
[0064]
[0065] The welding test conditions of the above embodiments and comparative examples are shown in Table 6. The welding joint forms used are as follows: Figure 1 As shown, the thickness of the welded part is 12 mm, the V-groove angle is 45°, and the weld bottom distance is 12 mm.
[0066] Table 6 Welding test conditions
[0067]
[0068] The performance design requirements of the present invention for the weld metal of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosive environment are:
[0069] Room temperature tensile property requirements of weld metal: yield strength R p0.2 ≥210MPa, tensile strength R m≥530MPa, elongation A≥30%; room temperature impact performance requirements: Akv2≥35J; the corrosion rate of the weld metal after immersion in simulated medium conditions (95℃, 6M nitric acid solution) until the corrosion rate is stable is ≤0.3mm / a; weld metal structure requirements: austenite + δ ferrite two-phase structure, FN value 1 to 10. The room temperature tensile performance test standard is GB / T 2652-2008, the high temperature tensile performance test standard is GB / T 228.2-2015, the room temperature impact performance test standard is GB / T2650-2008, and the corrosion performance test standard is JB / T 7901-1999.
[0070] It can be seen from Examples 1 to 5, Comparative Examples 1 to 2 and Tables 1 to 5 that:
[0071] The chemical composition of the welding wire designed by the present invention is adopted. The chemical composition of the welding wires in Examples 1 to 5 is within the scope of the technical solution of the present invention, and the weld metal meets the performance design requirements of the present invention. In Comparative Examples 1 and 2, the Ni content of the welding wire is 18.9% and 16.9%, respectively, which is not within the scope of the technical solution of the present invention (14.5% to 16.0%). The increase in Ni content leads to a lower content of delta ferrite (see Table 4, the FN values are all less than 1.0), an increase in crack sensitivity, and cracks appear in the weld metal (see Figure 2 ). Therefore, the toughness and plasticity of the weld metal are deteriorated, resulting in its room temperature elongation of only 6.5% and 16.2%, and the elongation at 100°C is only 7.5%, and the room temperature impact energy is 35J and 29J, respectively. It can be seen that the room temperature elongation and impact energy of the weld metal do not meet the design requirements of the present invention (room temperature elongation A ≥ 30%; room temperature impact energy Akv2 ≥ 35J). As can be seen from Table 5, the corrosion rate of the weld metal of the welding wires of Examples 1 to 5 is less than 0.3mm / a, which fully meets the performance design requirements.
[0072] The implementation results show that the welding wire of the present invention is suitable for welding austenitic stainless steel parts used in high-temperature concentrated nitric acid environments such as nuclear power or petrochemicals, and the welding process is stable, spatter is small, and the process performance is good. After welding with the ultra-low carbon high-Si austenitic stainless steel welding wire of the present invention for high-temperature concentrated nitric acid corrosion environment, a weld with excellent mechanical properties can be obtained, and the crack sensitivity is low, which meets the requirements of the high-temperature concentrated nitric acid corrosion service environment.
Claims
1. An ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance, characterized in that: The chemical composition of the welding wire is as follows, by weight percentage: C≤0.03%, Mn 0.3%~1.6%, Si 3.5%~4.5%, P≤0.01%, S≤0.01%, Cr 18.5%~20.5%, Ni 14.5%~16.0%, Mo≤1.1%, Nb≤0.15%, N0.03%~0.12%, Cu≤0.1%, Co≤0.06%, Al≤0.05%, V≤0.05%, and the balance is iron.
2. The ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to claim 1, characterized in that: The content of each group of elements in the welding wire is any one or more of the following a to g: a. The Cr content in the welding wire is further set to Cr: 18.5% to 19.0%, or further set to Cr: 19.0% to 19.6%, or further set to Cr: 19.6% to 20.5%; b. The Si content in the welding wire is further set to Si: 4.0% to 4.4%; c. The Ni content in the welding wire is further set to Ni: 14.5% to 15.0%, or further set to Ni: 15.0% to 16.0%; d. The nitrogen content in the welding wire is further set to N: 0.03% to 0.07%, or further set to N: 0.07% to 0.10%, or further set to N: 0.10% to 0.12%; e. The Mn content in the welding wire is further set to Mn: 0.3% to 0.9%, or further set to Mn: 0.9% to 1.3%, or further set to Mn: 1.3% to 1.6%; f. The Nb content in the welding wire is further set to Nb≤0.02%; g. The Mo content in the welding wire is further set to Mo≤0.02%.
3. The ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to claim 1 or 2, characterized in that: The content of each group of elements in the welding wire is any one or more of the following a to f: a. The Cu content in the welding wire is further set to Cu≤0.05%, or further set to Cu≤0.02%, or further set to Cu≤0.01%; b. The Co content in the welding wire is further set to Co≤0.03%, or further set to Co≤0.02%, or further set to Co≤0.01%; c. The Al content in the welding wire is further set to Al≤0.02%, or further set to Al≤0.01%; d. The V content in the welding wire is further set to V≤0.02%, or further set to V≤0.01%; e. The P content in the welding wire is further set to P≤0.005%; f. The S content in the welding wire is further set to S≤0.003%.
4. An application of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to any one of claims 1 to 3, characterized in that: This welding wire is used for welding austenitic stainless steel parts used in high temperature concentrated nitric acid environment in nuclear power or petrochemical industries.
5. The use of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to claim 4, characterized in that: The wire welding process adopts TIG welding, the joint form is butt joint, the welding current is 150-200A, the arc voltage is 10-15V, the current type / polarity is direct current positive connection mode, and the welding speed is 0.05-0.15m / min.
6. The use of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to claim 5, characterized in that: The test pieces were welded by a multi-layer and multi-pass deposition method, and the interlayer temperature during the welding process was lower than 100°C.
7. The use of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to claim 5, characterized in that: Select welding wire with specification of Φ2.0mm for welding process.
8. The use of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to claim 5, characterized in that: During the wire welding process, high-purity argon gas with a volume purity of ≥99.995% is used for arc protection, and the argon gas flow rate is 12 to 20 L / min.
9. The use of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to any one of claims 5 to 8, characterized in that: Room temperature tensile properties of the weld metal obtained after welding: yield strength R p0.2 ≥210MPa, tensile strength R m ≥530MPa, elongation A≥30%; room temperature impact performance: Akv2≥35J; weld metal structure requirements: austenite + delta ferrite two-phase structure, FN value 1~10.
10. The use of the ultra-low carbon high Si austenitic stainless steel welding wire for high temperature concentrated nitric acid corrosion resistance according to any one of claims 5 to 8, characterized in that: The corrosion rate of the weld metal is ≤0.3mm / a when immersed in a nitric acid solution with a molar concentration of 6M at 95°C under simulated medium conditions until the corrosion rate stabilizes.
Citation Information
Patent Citations
Ultralow-carbon austenitic welding wire material for welding of stainless steel
CN102319965A
Tough corrosion-resistant three-phase stainless steel, preparation method thereof and stainless steel product
CN115717221A
Austenitic stainless steel welding wire and application thereof
CN117733400A
Heat-resistant austenitic stainless steel
EP0434887A1
Corrosion-resisting austenitic-ferritic stainless steel
GB1376390A
Cited By
Stainless steel wire with ultralow oxygen and carbon content, preparation method and stainless steel welding wire
CN120170326A